2020
DOI: 10.15252/embr.201948671
|View full text |Cite
|
Sign up to set email alerts
|

The mechanoreceptor DEG‐1 regulates cold tolerance in Caenorhabditis elegans

Abstract: Caenorhabditis elegans mechanoreceptors located in ASG sensory neurons have been found to sense ambient temperature, which is a key trait for animal survival. Here, we show that experimental loss of xanthine dehydrogenase (XDH‐1) function in AIN and AVJ interneurons results in reduced cold tolerance and atypical neuronal response to changes in temperature. These interneurons connect with upstream neurons such as the mechanoreceptor‐expressing ASG. Ca2+ imaging revealed that ASG neurons respond to warm temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 50 publications
(86 reference statements)
1
50
0
1
Order By: Relevance
“…To investigate whether TRPVs are capable of conferring thermal sensitivity to warm stimuli, we expressed OSM-9 and OCR-2 TRPVs in the right ASE (ASER) gustatory neuron. ASER was used because it is a non-warmth-sensing neuron that has previously been used in reconstitution analysis to measure temperature sensitivities of novel temperature receptors, such as rGCs and a degenerin/epithelial Na + channel-type mechanoreceptor involved in thermotaxis and cold tolerance, respectively 7 , 13 . ASER acts as a cool-sensing neuron in which GLR-3, a kainate-type glutamate receptor, functions as a cool-sensing receptor 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate whether TRPVs are capable of conferring thermal sensitivity to warm stimuli, we expressed OSM-9 and OCR-2 TRPVs in the right ASE (ASER) gustatory neuron. ASER was used because it is a non-warmth-sensing neuron that has previously been used in reconstitution analysis to measure temperature sensitivities of novel temperature receptors, such as rGCs and a degenerin/epithelial Na + channel-type mechanoreceptor involved in thermotaxis and cold tolerance, respectively 7 , 13 . ASER acts as a cool-sensing neuron in which GLR-3, a kainate-type glutamate receptor, functions as a cool-sensing receptor 8 .…”
Section: Resultsmentioning
confidence: 99%
“…5 a, OSM-9 OCR-2). A previous report showed that OSM-9, OCR-1, and OCR-2 cooperatively control thermosensory activity in C. elegans , with OCR-1 acting as a negative regulator of TRPV channels 13 , 16 , although it remains unclear whether OCR-1 forms a heterochannel complex with OSM-9 and OCR-2. A warm stimulus (~ 36 °C) evoked detectable inward currents in Xenopus oocytes simultaneously injected with osm-9 , ocr-2, and ocr-1 cRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…。 著者らは,行動に依存しない神経回路情報処理の実験系 として線虫の「低温耐性現象」を指標に解析を行ってきた。 低温耐性とは,25 ℃で飼育した線虫を2℃に移すと死滅す るのに対し,15 ℃で飼育した線虫を2℃に移しても生存で きる現象である。さらに,25 ℃で飼育した個体を,わずか 3-5時間15 ℃に置くことで2 ℃でも生存できるようにな る低温馴化現象も見つかってきた 18,19,28) (図1) 。 低温耐性における温度応答メカニズムの分子・組織機構 は少しずつ明らかになってきている 11,17,18,22,24,27,29)…”
unclassified